2016
DOI: 10.2147/oajsm.s101995
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sex, age, and race experience on pacing profiles during the 90 km Vasaloppet ski race

Abstract: The purpose of this study was to investigate pacing-profile differences during the 90 km Vasaloppet ski race related to the categories of sex, age, and race experience. Skiing times from eight sections (S1 to S8) were analyzed. For each of the three categories, 400 pairs of skiers were matched to have a finish time within 60 seconds, the same start group, and an assignment to the same group for the other two categories. Paired-samples Student’s t-tests were used to investigate sectional pacing-profile differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
5

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 40 publications
1
41
5
Order By: Relevance
“…Cross-country skiing, one of the earliest known winter physical activities (6), is a sport of high popularity especially in countries characterized by low temperatures and high snowfall, especially in Scandinavia (5). Cross-country skiing is a form of skiing where skiers rely on their own locomotion to move across snow-covered terrain.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-country skiing, one of the earliest known winter physical activities (6), is a sport of high popularity especially in countries characterized by low temperatures and high snowfall, especially in Scandinavia (5). Cross-country skiing is a form of skiing where skiers rely on their own locomotion to move across snow-covered terrain.…”
Section: Introductionmentioning
confidence: 99%
“…The 'Vasaloppet' is the oldest and longest XC skiing race in the world and has the largest rates of participation [6]. The race is a total distance of 90 km; it starts in Sälen and finishes in Mora, and includes seven stations which define eight splits (▶Table 1).…”
Section: The Racementioning
confidence: 99%
“…In 10-and 15-km XC skiing races in World Cup, World Championships and Olympic events, slower men skiers were characterized by a relatively fast start, but no difference was found in women [21]. A study on a relatively small sample of finishers in the Vasaloppet skiing race showed that women had a more even profile than men [6]. In 100-km running, fast men runners started relatively slower in the first parts of the race, but this was not the case for women [26].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations